"You want to build a wall?": politics in the music classroom. Issue 4 (14th September 2022) - VanDeusen, Andrea J.
Abstract: In recent years, the United States and Western world experienced rises in nationalism, xenophobia, ethnocentrism, and anti-immigrant racism, with heightened awareness of these issues in the wake of the 2016 United States presidential election. In this article, I explore the impacts of the political climate on preservice music teachers' field experiences in predominately Arab, Muslim, immigrant, and refugee schools, discuss preparedness to navigate the impacts of a divisive political climate on students and in schools, and offer policy recommendations for school administrators, in-service teachers, and music teacher educators to prepare and support politically aware and politically competent music educators whose work exists within the larger frame of local and global political realities.